CHANGES IN BIOLOGICAL PROPERTIES OF SOILS AS A RESULT OF CHEMICAL POLLUTION (Scientific journal of the Fergana State University, 2024)
Pollution of the environment, including soil, with chemical pollutants is increasing year by year, which leads to a decrease in soil fertility as a result of negative effects on the chemical, physical and biological condition of the soil. As a result of chemical pollution of the soil, first of all, the microbiological world of the soil changes, the activity of enzymes decreases, and the ability to self-clean the soil is lost. Under the influence of chemical pollutants, it was observed that the activity of microorganisms decreased by 1.5-2 times in the soils around the Ohangaron cement plant and Angren thermal power plant.